HUKUM DAKWAH DALAM AL-QUR' AN DAN HADIS - Desi Syafriani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
Da'wah in general means an activity of hailing or inviting others to do well. While the science of da'wah defined a science about the activities of da'wah from input, process until the output or until the da’wah succeed. Beside the Qur’an, hadith also commands or to do da'wah. The law of da'wah seems to be different for each person depending on the situation and conditions of that person in legal view. Abu Sa'id Al-Khudry ra said, I heard the Messenger of Allah (SAW), decree